Perancangan Pemadam Api Otomatis Berbasis Arduino Uno Menggunakan Metode Quality Function Deployment (QFD) - Putri Utami, Intan; Gavin Azarya, Bintang; Ahmad Ryan, Aditya; Kalvin, Elroy; Muslimin, Muslimin; Luqyana, Dhiya; Muhamad, Azam Millah (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
The automatic fire extinguishing industry continues to evolve to improve fire detection and response efficiency, especially for small sectors like foodcourt SMEs and small shops, which are vulnerable to fire risks. This study aims to design an affordable and effective automatic fire extinguishing system based on Arduino Uno, using the Quality Function Deployment (QFD) method and House of Quality (HoQ) to translate customer needs, such as fast fire detection, minimalist design, low power consumption, and cost-efficient production, into technical specifications. The system integrates a flame sensor for fire detection, DC motors for movement, and a water pump for fire extinguishing, designed modularly to operate in confined spaces. The research findings show that this design not only meets customer needs but also provides a practical and cost-effective solution to enhance fire safety in small sectors, with a system that is fast, efficient, and affordable.